Bernhard Heisig and the fight for modern art in East Germany - Eisman, April A., 1972- (Studies in German literature, linguistics, and culture., 2018)
East German studies today is thriving. Scholars have shown East Germany to be a complex society where culture played an important, if contested, role in the making of the socialist person. In English-language scholarship, however, the visual arts-and especially painting-have been largely ignored, the result of the misperception that East German art was little more than kitsch or propaganda. This book focuses on one of East Germany's most successful artists as a point of entry into the vibrant art world of the "other" Germany. 0In the 1980s, Bernhard Heisig (1925-2011) was praised on both sides of the Berlin Wall for his neo-expressionist style and his commitment to German history and art. Chancellor Helmut Kohl chose him to paint his official portrait, major museums collected his work, and in 1989 he had a major solo exhibition in West Germany. After unification, Heisig was a focal point in the Bilderstreit, a virulent debate over what role East German art should play in the new Germany. Challenging current understandings of Heisig and East German art, this book focuses on Heisig's little-known fight for modern art in East Germany. Examining major debates of the 1960s, it shows the key role he played in expanding the country's art from the limits of Soviet-style socialist realism to a socialist modernism that later gained recognition in the West